A ROUTE EFFICIENCY ANALYSIS BASED ON DATA ENVELOPMENT ANALYSIS: AN APPLICATION TO AGRICULTURE - Andrić Gušavac, Bisera; Savić, Gordana; Martić, Milan (Faculty of Economics-Skopje, SS. Cyril and Methodius University in Skopje, 2020)
This study employs data envelopment analysis (DEA) approach to evaluate the performance of agricultural aircraft routes. In the context of agricultural aircraft usage, not enough attention has been paid to the efficiency study of the routes in agricultural operations. Aircraft are used in agriculture to perform various treatments on agricultural land. Presumptions in this study are that a land is divided into parcels and one type of treatment must be performed on these parcels. Also, the considered operation is performed by the agricultural aircraft and the size of the analyzed land implies that all parcels cannot be treated in one route, so there are multiple routes which have to be completed. Here, we propose application of output oriented CCR DEA model on one set of routes in order to determine relatively efficient routes. Proposed inputs for the application of the DEA method are: tank capacity of an aircraft and total cost of parcel treatment in one route. Proposed outputs are: total treated land area (total area of all parcels in route) in one route and percentage share of effective flight in the total distance traveled in one route. In this way relatively efficient routes can be selected, and some further analysis of relatively inefficient routes can be made in order to see what changes can be done in inputs and / or outputs of these inefficient routes to improve their performance.
Keywords: Data envelopment analysis; Route efficiency; Agriculture